Impact of quality of improvement in operation management towards customerss satisfaction and company's performance - Theo Hansardi, Muhammad; Nizar, Adirizal (The Indonesian Journal of Business Administration, 2018)
Abstract. In every year, demand of automotives industry always increase, which will impact into the number of accident. This could be the opportunities for body repair industry. The demand of products/services in body repair company was really high, on the other hand, there is low level of competitor in the body repair market. To take this opportunities, every company that want to survive in the market need to provide something different. Hanjaya Motor is an automotive industry that focus on customers’ satisfaction and quality product. Hanjaya provide high level of quality with an affordable price in the market. However there are several problem such as quality control, low level of employees’ performance and defect product in the Hanjaya’s production which will be obstacles in the business to taking the opportunities in the market. In this research, Author discuss about evaluating Hanjaya’s performance starting from evaluatin the market situation by conduct Porter 5 Forces, understand which factors that have have been influenced in compayn performance by Macro Micro Environment, understand the Hanjaya’s company by SWOT Analysis, continue to observe the target market of the company by using STPD Theory, understand the operation process by using Six-Sigma Theory and DMAIC Framework. Which leads Author to evaluate the quality of company by using Quality Control and Cost of Quality Theory. And the last step is find and solve the core problem of the company by using Fishbone framework.  The result of this research is there are 3 main problem in Hanjaya, which is Quality Control, Employees’ performance, and Defect products. Lacks of quality control affect the company to for having low level of competitors that will leads the production fail and producting defect products. In order to solve the problem, Hanjaya need to increase the quality control by providing more inspection division that act like monitoring and controlling in body repair process.